O papel de abelhas nativas e invasora na seleção diferencial de nicho e importância em uma rede mutualística - Santos, Joyce dos (2021)
The global decline in biodiversity has drawn attention to the consequences of species loss in maintaining ecosystem functioning. The anthropic processes of destruction of plant species, the intensification of land use, the use of agrochemicals and the introduction of exotic species have adverse effects on the diversity of pollinators. Such processes together with the effects of climate change affect the pollination service. The inclusion of tools that inform about the properties of biodiversity, as well as its organization and its relationship with ecosystem processes and services, enable a more complete monitoring of communities. Functional diversity can be used for this purpose. This can be represented by the richness of attributes in a community, the number of emitted groups and the volume of niche occupied by the species. Hymnoptera is a group considered hyperdiverse and comprises the largest number of pollinators from natural areas and agricultural ecosystems. Apis mellifera tends to be a more important species for the pollination process and often native species are neglected. Thus, the objective of this work is to verify the existence of niche sharing, when comparing social stingless bees Trigona spinipes and Trigona hialinata and solitary bees of the genus Centris with the niche of A. mellifera, as well as the importance of species in structuring the network interaction with flowering plants. For this we raise the following hypothesis, regardless of being native or invasive, social species present a greater degree of generalism and importance in their interactions with their resources than solitary species. The results of this work demonstrated that the two native social Trigona species have a greater niche overlap with A. mellifera. While the Centris species, which are solitary, have a different niche. The results also show that social species are more important in structuring interactions and that the native social species T. spinipes stands out as the most important among those analyzed. Thus, we can infer that although A. mellifera is non-native, it exploits resources similarly to native ones. In general, we can say that different bee species can coexist in the same habitat, regardless of whether they are native or invasive. Furthermore, sociality presents itself as an important trait mediating the importance of species in the exploitation of resources.